2021
DOI: 10.1186/s12886-020-01790-6
|View full text |Cite
|
Sign up to set email alerts
|

Thygeson’s superficial punctate keratitis (TSPK): a paediatric case report and review of the literature

Abstract: Background Thygeson’s superficial punctate keratitis (TSPK) is reportedly a rare disease with an insidious onset, numerous remissions and exacerbations, and a long duration. The corneal lesions are elevated, whitish–grey in colour, and granular in the intraepithelium. A few reported cases of TSPK exist, and paediatric experience is limited. Due to the unknown aetiology and controversial treatment strategies for TSPK, we performed a literature review to summarize the criteria for the diagnosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…In addition, topical corticosteroids may permit or encourage subepithelial lipid accumulation or deposition and cause additional corneal opacity [ 10 ]. In long-term management of IMMK, topical immunomodulators may be a better choice compared to topical corticosteroids because they are associated with lower incidence of ocular and systemic side effects, and the effect of topical immunomodulators as lacrimostimulants may potentiate the healing of the lesions [ 3 10 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, topical corticosteroids may permit or encourage subepithelial lipid accumulation or deposition and cause additional corneal opacity [ 10 ]. In long-term management of IMMK, topical immunomodulators may be a better choice compared to topical corticosteroids because they are associated with lower incidence of ocular and systemic side effects, and the effect of topical immunomodulators as lacrimostimulants may potentiate the healing of the lesions [ 3 10 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive action of tacrolimus is much greater than that of cyclosporine [ 12 ], and both patients showed promising results when 0.03% tacrolimus was prescribed, suggesting that tacrolimus may be considered when other medications are ineffective or cause complications. In humans, Thygeson’s superficial punctate keratopathy (TSPK) presents similar morphology and response to topical immunosuppressants [ 11 ], and previous studies have reported that topical 0.02% tacrolimus is a safe and effective alternative when unresponsive to topical steroids in TSPK [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Although the onset is typically in the second or third decades of life, recent pediatric cases have been described. 9 The duration of the disease has been reported as long as 40 years. 9 The duration of the disease has been reported as long as 40 years.…”
Section: Epidemiology and Etiologymentioning
confidence: 99%
“…9 The duration of the disease has been reported as long as 40 years. 9 The duration of the disease has been reported as long as 40 years. 10 Over the years, many hypotheses have been introduced regarding its origin, among which are infectious, genetic, and inflammatory factors.…”
Section: Epidemiology and Etiologymentioning
confidence: 99%